Association between neutrophil percentage-to-albumin ratio and breast cancer in adult women in the US: findings from the NHANES - Liang, Huikai; Pan, Kelun; Wang, Jiayi; Lin, Jianqing (Frontiers in Nutrition, 2025)
BackgroundAn increasing number of studies suggests an association between systemic inflammation, nutritional status, and cancer. However, the relationship between the prevalence of breast cancer (BC) and the neutrophil-percentage-to-albumin ratio (NPAR), a recently identified biomarker of inflammation, is not well established. Therefore, this study aims to investigate the relationship between BC risk and the NPAR.MethodsThis study included 18,726 participants from the National Health and Nutrition Examination Survey (NHANES) conducted between 2001 and 2018. The NPAR was used to assess inflammation and nutritional status. Statistical methods such as multivariate logistic regression, subgroup analysis, and restricted cubic spline (RCS) analysis were conducted to investigate the influence of NPAR on the prevalence of BC. In addition, propensity score matching was employed to further validate the findings.ResultsThe logistic regression results showed that the prevalence of breast cancer is significantly associated with the NPAR (OR = 1.05; 95% CI = 1.02–1.09, p = 0.003). In comparison to participants in the lowest quartile, Q1, the prevalence of breast cancer increased by 5% for those in Q2 (p = 0.745), 3% for those in Q3 (p = 0.032), and 38% for those in Q4 (p = 0.018) with a higher NPAR. In addition, subgroup and RCS analyses showed that the NPAR and BC prevalence were positively correlated. Furthermore, a significant association was observed between the NPAR and marital status. The significance of traits was assessed using mean decrease accuracy (MDA) and mean decrease impurity (MDI). These measures of random forest modeling showed that NPAR is one of the major factors affecting the prevalence of BC. Furthermore, linear analysis demonstrated a correlation between a high NPAR and increased total testosterone and sex hormone-binding globulin (SHBG) levels.ConclusionA significant association was observed between a high NPAR and a higher prevalence of breast cancer, which could be attributable to sex hormone levels. This finding suggests that the NPAR may serve as a biomarker for BC in adult women in the US.